Boi roubado: uma tradição de trabalho em festa na região sisaleira - França, Daiane de Araújo (2015)
The dissertation entitled Stolen Boi: a party in labor tradition in sisal region studies the cultural expression of Bahia sisal region called Stolen Boi. It consists of a playful collective expression held in Sisal territory communities, integrating agricultural work, songs, dances, performers and linguistic elements and the presence of rituals and to man the way and the peasant woman. The choice of this theme grew out of curiosity to understand the symbology of a group of Stolen Boi, as well as its impact and contribution to the strengthening of sisal culture. To mount the analysis corpus, consisting of the work songs and the performative elements, the methodological procedures of Oral History, Anthropology and Ethnography, passing by the theories of memory and cultural hybridity were used. Without ignoring the traditional folklore studies (Camara Cascudo), contemporary scholars, like Alcoforado (1989, 1990, 2008), Anderson (2009), Bauman (2005) and Canclini (2008), Paul Zumthor (1993, 1997, 2007), give support to the text. Throughout this trodden path sought to show that since the pioneering work by the current approaches to culture, much progress has been made in relation to the theoretical and methodological apparatus that area. In this sense, another aspect becomes relevant: contemporary studies seek to promote the various languages and demonstrations that are in the cultural text, moving away from the disappearance of fear of the traditions surrounding folklorists and made them believe in redemption through the registry (ALBUQUERQUE JÚNIOR, 2007). How is ratified in all the work, traditions (re)invent (HOBSBAWM, 1997) so that the man, as a producer and historical agent, maintain and reframes the culture of your community. This dynamic inherent in the traditions and culture demands more attention to the researcher's speech and the specificities of each social group, as well as greater flexibility and adequacy of theories and tools of study.